Current Concepts in Dental Implantology 2015
DOI: 10.5772/59487
|View full text |Cite
|
Sign up to set email alerts
|

Bone Substitute Materials in Implant Dentistry

Abstract: Although bone autografts have been routinely used as "gold standard" for reconstruction/ replacement bone defects, because they have osteogenic, osteoinductive, osteoconductive properties, they have a high number of viable cells and are rich in growth factors. However, the use of autograft is limited by several factors, being one of them the insufficient amount of donor tissue. Therefore, bone substitute materials have been extensively studied in order to develop an ideal material for substitution of bone graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 167 publications
(207 reference statements)
0
24
0
Order By: Relevance
“…Delayed cell proliferation was further observed on similar scaffolds during the first days by others . Superficial resorption processes and an accelerated dissolution as a result of CDHAs high surface area of about 50 m 2 /g can lead to a reduced rate of cell proliferation . BSP coating might compensate for the material surface effects via its integrin‐binding arginylglycylaspartic acid (RGD) sequence.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Delayed cell proliferation was further observed on similar scaffolds during the first days by others . Superficial resorption processes and an accelerated dissolution as a result of CDHAs high surface area of about 50 m 2 /g can lead to a reduced rate of cell proliferation . BSP coating might compensate for the material surface effects via its integrin‐binding arginylglycylaspartic acid (RGD) sequence.…”
Section: Discussionmentioning
confidence: 80%
“…39,40 Superficial resorption processes and an accelerated dissolution as a result of CDHAs high surface area of about 50 m 2 /g can lead to a reduced rate of cell proliferation. [41][42][43][44] BSP coating might compensate for the material surface effects via its integrin-binding arginylglycylaspartic acid (RGD) sequence. Several studies demonstrated enhanced cell attachment via the RGD-domain of BSP.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Recently, numerous studies have reported that biodegradable calcium phosphates, such as alpha tricalcium phosphate (α-TCP, α-Ca 3(PO4)2), β-TCP, carbonate apatite, and octacalcium phosphate (OCP), can be substituted by the bone tissue over time through the bone remodeling processes [1][2][3][4] . Some biodegradable calcium phosphates have been extensively investigated and applied for treating the site of bone defects to stabilize dental implants 5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, allografts and xenografts have been used as alternatives for bone repair, although they may promote rejection, and diseases can be transmitted when not properly chemically processed (Suchanek, Yoshimura, 1998). For these reasons, alternative bone substitutes auto, allo and xenografts to replace auto, allo, and xeno bone grafts (Saska et al, 2015) which contain materials with similar characteristics to bone tissue, such as osteoconductive, osteoinductive and osteogenic properties for decreasing immunogenic and compatibility problems (Saska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of those, poly(lactic-co-glycolic acid) (PLGA) is a biodegradable aliphatic polyester polymer obtained from hydroxyl acids (De Lima et al, 2011); it is used in several biomedical applications, such as tissue and genetic engineering and drug delivery (Cieślik et al, 2009). This polymer has the capacity to modulate the mechanical properties of others compounds and provide versatility in their structure (Saska et al, 2015), and it can be used as supporting or stabilizing elements by creating composites based on them (Cieślik et al, 2009). The association with other compounds provides biocompatibility, bioactivity, satisfactory mechanical properties, and osteoconduction, which makes them potential materials in regenerative medicine therapies (Saska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%